Blue Accounting dan Wirausaha Teripang Laut: Studi Kasus di Desa Torosiaje, Kecamatan Popayato, Kabupaten Pohuwato - Helton Wira Nugraha R.A Umar; Nilawaty Yusuf; Muliyani Mahmud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find forms of Blue Accounting practices in sea cucumber entrepreneurs (Case Study in Torosiaje Village, Popayato District, Pahuwato Regency). This research uses descriptive qualitative methods, data collection uses observation, interviews and documentation. Based on the research results, it can be stated that sea cucumber entrepreneurs in Torosiaje Village have implemented the principles of Blue Accounting where the fishing community and sea product collectors focus on sea cucumbers, starting from cultivating sea cucumbers naturally by avoiding catching young sea cucumbers or too small can help ensure that they have a chance to reproduce before being caught. So Blue Accounting has a big impact on sea cucumber entrepreneurship, where the big impact of Blue Accounting itself can be seen from how it helps sea cucumber entrepreneurs monitor and manage sea cucumber stocks in a sustainable manner and run businesses by prioritizing the environment as an asset in their business activities.